2020
DOI: 10.1101/2020.01.31.928150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evolutionary trade-off between parasite virulence and dispersal at experimental invasion fronts

Abstract: 21Understanding the occurrence and spatial spread of infectious disease is a major challenge to 22 epidemiologists and evolutionary biologists. Current theory predicts the spread of highly 23 exploitative parasites at the front of spreading epidemics. However, many parasites rely on the 24 dispersal of their hosts to spread to new habitats. This may lead to a conflict between local 25 transmission and spatial spread, counteracting selection for highly virulent parasites. Yet, there 26 are no experimental… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…More specifically, in a host-parasite system, prevalence could be a good predictor of a patch future condition only at high parasite virulence (Deshpande et al, 2020). In our system, Holospora undulata generally reduces survival and reproductive success of P. caudatum (Restif & Kaltz, 2006;Nørgaard et al, 2020), which is also reflected by differences in population density between uninfected control and infected microcosms in the present experiment (density uninfected control: 288 mL -1 , ± 103; infected: 139 mL -1 , ± 91 SE). Hence, we might speculate that some strains could have had an evolutionary history with a highly virulent parasite in the wild.…”
Section: Context-dependent Plasticitymentioning
confidence: 81%
See 3 more Smart Citations
“…More specifically, in a host-parasite system, prevalence could be a good predictor of a patch future condition only at high parasite virulence (Deshpande et al, 2020). In our system, Holospora undulata generally reduces survival and reproductive success of P. caudatum (Restif & Kaltz, 2006;Nørgaard et al, 2020), which is also reflected by differences in population density between uninfected control and infected microcosms in the present experiment (density uninfected control: 288 mL -1 , ± 103; infected: 139 mL -1 , ± 91 SE). Hence, we might speculate that some strains could have had an evolutionary history with a highly virulent parasite in the wild.…”
Section: Context-dependent Plasticitymentioning
confidence: 81%
“…In our analysis we observed that the dispersal outcome was affected by the identity of the host strains ( Figure 1A-B). Previous studies reported that infection by H. undulata reduced dispersal in P. caudatum (Fellous et al, 2011;Nørgaard et al, 2020), which was related to a reduction in survival and reproduction. The explanation for a reduced dispersal can easily be connected to the negative effect that a parasite may have on its host locomotory ability (Horky et al, 2014;Binning et al, 2017).…”
Section: State-dependent Plasticitymentioning
confidence: 91%
See 2 more Smart Citations
“…Individuals hence allocate 20 limited amounts of energy to some traits at the detriment of others (Stearns 1989). Many 21 examples of such trade-offs have been thoroughly documented in various organisms ranging 22 from plants to microorganisms (Lind et al 2013;Nørgaard et al 2020). For example, lifespan 23 and reproductive rate are constrained by a trade-off (Chippindale et al 2004;Flatt 2011;24 Travers, Garcia-Gonzalez and Simmons 2015) because endogenous resources allocated to 25 reproductive functions are not available for somatic and repair functions (Flatt, 2011;26 Schwenke, Lazzaro and Wolfner, 2016).…”
Section: Introduction 14mentioning
confidence: 99%